Adam's Genealogy : A handbook - Yaacob, Solehah@Nik Najah Fadilah (SH Lingua Edu Enterprise, 2020)
The differences in opinion in the genealogy for some references are to the manner in which the information was presented orally prior to its writing. It is interesting that the version presented by the Islamic sources is far more data-oriented when compared to the views of Orientalists like Cornellius and his contemporaries who focus on Ishmael and his descendants alone. In fact, many secondary sources have supported the Islamic revelation in that Adam and Eve were the first people to inhabit the earth. However, for some it is considered merely a matter of myth and legends that are based only on oral history, and this view is incorrect. Arab sources have confirmed that the existence of their nation dates back to the time of Abraham. Clearly, such information is no fiction. Moreover, this statement indirectly reveals that the Arabic language has existed for a long time, since the emergence of the proto-Arabs themselves. According to linguists, Saba`, Yemen is among the earliest places in which this language appears. Although the Himyarite or Thamudic language is not the same as the Arabic language recorded in the Qur'an, it is nonetheless considered one of the dialects of this language. This is because these dialects fall within the Fertile Crescent region of the Arabian Peninsula. It is believed that Arabic has existed for a long time, and the notion that another language once existed is incorrect. This is because even though it shows differences in pronunciation or writing, these changes simply represent the evolution of the language itself without changing the original identity and grammar of the language. This is because the most significant aspect of Arab identity is the language even though it came in different dialects. Thus, the basic nature of a certain language must come from the same parent language; even though it has gone through many centuries of evolutionary processes, or even if it came from different places but is still within the framework of the original land, it will still belong to the same language family.